Philosophy of Biology in OBI - Skoczny, Włodzimierz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
This research in the philosophy of biology in OBI was focused on the problems related to the nature and evolution of life. Special attention is paid to issues in the history of biology, evolutional theism, and neurophysiology.